Efficient synthesis of a maghemite/gold hybrid nanoparticle system as a magnetic carrier for the transport of platinum-based metallotherapeutics - Štarha, Pavel; Smola, David; Tuček, Jiří; Trávníček, Zdeněk (International journal of molecular sciences, 2015)
The preparation and thorough characterization of a hybrid magnetic carrier system for the possible transport of activated platinum-based anticancer drugs, as demonstrated for cisplatin (cis-[Pt(NH3)2Cl2], CDDP), are described. The final functionalized mag/Au-LA-CDDP* system consists of maghemite/gold nanoparticles (mag/Au) coated by lipoic acid (HLA; LA stands for deprotonated form of lipoic acid) and functionalized by activated cisplatin in the form of cis-[Pt(NH3)2(H2O)2]2+ (CDDP*). The relevant techniques (XPS, EDS, ICP-MS) proved the incorporation of the platinum-containing species on the surface of the studied hybrid system. HRTEM, TEM and SEM images showed the nanoparticles as spherical with an average size of 12 nm, while their superparamagnetic feature was proven by 57Fe Mössbauer spectroscopy. In the case of mag/Au, mag/Au-HLA and mag/Au-LA-CDDP*, weaker magnetic interactions among the Fe3+ centers of maghemite, as compared to maghemite nanoparticles (mag), were detected, which can be associated with the non-covalent coating of the maghemite surface by gold. The pH and time-dependent stability of the mag/Au-LA-CDDP* system in different media, represented by acetate (pH 5.0), phosphate (pH 7.0) and carbonate (pH 9.0) buffers and connected with the release of the platinum-containing species, showed the ability of CDDP* to be released from the functionalized nanosystem.
Keywords: nosiče léků; Drug Carriers; fotoelektronová spektroskopie; biologický transport; Thermogravimetry; Photoelectron Spectroscopy; Spectroscopy, Mossbauer; diferenční termická analýza; koncentrace vodíkových iontů; nanotechnologie; Biological Transport; Spectrophotometry, Infrared; Nanotechnology; Ferric Compounds; magnetické jevy; Platinum; spektroskopie Mossbauerova; Magnetic Phenomena; Metal Nanoparticles; železité sloučeniny; spektrometrie rentgenová emisní; Hydrogen-Ion Concentration; zlato; termogravimetrie; spektrofotometrie infračervená; Gold; spektrofotometrie atomová; platina; kovové nanočástice; Differential Thermal Analysis; Spectrophotometry, Atomic; Spectrometry, X-Ray Emission